Anatomy of the Orbit - Lieber, Stefan; Fernandez-Miranda, Juan C. (Journal of Neurological Surgery Part B: Skull Base, 2020)
The orbit is a paired, transversely oval, and cone-shaped osseous cavity bounded and formed by the anterior and middle cranial base as well as the viscerocranium. Its main contents are the anterior part of the visual system, globe and optic nerve, and the associated neural, vascular, muscular, glandular, and ligamentous structures required for oculomotion, lacrimation, accommodation, and sensation.A complex stream of afferent and efferent information passes through the orbit, which necessitates a direct communication with the anterior and middle cranial fossae, the pterygopalatine and infratemporal fossae, as well as the aerated adjacent frontal, sphenoidal, and maxillary sinuses and the nasal cavity.This article provides a detailed illustration and description of the microsurgical anatomy of the orbit, with a focus on the intrinsically complex spatial relationships around the annular tendon and the superior orbital fissure, the transition from cavernous sinus to the orbital apex. Sparse reference will be made to surgical approaches, their indications or limitations, since they are addressed elsewhere in this special issue. Instead, an attempt has been made to highlight anatomical structures and elucidate concepts most relevant to safe and effective transcranial, transfacial, transorbital, or transnasal surgery of orbital, periorbital, and skull base pathologies.
Keywords: orbit; microsurgical anatomy; extraocular muscles; annular tendon; annulus of Zinn; skull base; cranial nerves; optic nerve; oculomotor nerve; trochlear nerve; abducens nerve; trigeminal nerve; facial nerve; optic canal; superior orbital fissure; orbital apex; ciliary ganglion; ophthalmic artery